2021
DOI: 10.2807/1560-7917.es.2021.26.36.2100792
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a national increase in COVID-19 vaccination intention, the Netherlands, November 2020–March 2021

Abstract: The intention to get the COVID-19 vaccine increased from 48% (November 2020) to 75% (March 2021) as national campaigning in the Netherlands commenced. Using a mixed method approach we identified six vaccination beliefs and two contextual factors informing this increase. Analysis of a national survey confirmed that shifting intentions were a function of shifting beliefs: people with stronger intention to vaccinate were most motivated by protecting others and reopening society; those reluctant were most concerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…Third, and most consistent with literature prior to the COVID-19 pandemic, the social contract that binds parents to their children seems to have precedence over other social contracts in the community [ 25 , 31 , 59 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Third, and most consistent with literature prior to the COVID-19 pandemic, the social contract that binds parents to their children seems to have precedence over other social contracts in the community [ 25 , 31 , 59 ].…”
Section: Discussionsupporting
confidence: 60%
“…A frequent object of debate is whether to describe risks to the individual or community. Several studies prior to and during COVID-19 have been found to increase vaccination intention when vaccination is framed as a public good that helps create a layer of protection for vulnerable groups [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. With regards to parental intentions as well, ‘benefit to others’ has been established as an important motivating factor [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, a quantitative study in Dutch reported a similar finding. After introducing a safe vaccine comparable to those already available in the market, the factor in deciding to receive the vaccine becomes less important than other factors such as the cost or effectiveness of the vaccine [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, longitudinal research conducted before the vaccines were rolled-out observed a decrease in vaccination intention (Daly & Robinson, 2021;Fridman et al, 2021). Since the roll-out, most studies report an increase in vaccination intention over time (Bachtiger et al, 2021;Sanders et al, 2021;Thaker & Ganchoudhuri, 2021). Improving our understanding of people's intention to get vaccinated can help to stimulate vaccine uptake.…”
Section: Statement Of Relevancementioning
confidence: 99%